IGFBP-2 in cervical cancer development - Kaur, Gurjeet; Balasubramaniam, Shandra Devi; Yung, Jen Lee (Academic Press, 2020)
Objective: Increased expression of insulin-like growth factor binding protein 2, IGFBP-2, is associated with many cancers, though its role in cervical cancer is unclear. The aim of this study was to investigate the expression of IGFBP-2 protein and the transcriptomics profile of genes involved in the IGF signaling pathway during cervical cancer development. Design: Immunohistochemical expression of IGFBP-2 protein was semi-quantitatively assessed in tissue microarrays containing 9 normal cervix, 10 low grade cervical intraepithelial neoplasia (LGCIN), 10 high grade cervical intraepithelial neoplasia (HGCIN) and 42 squamous cell carcinoma (SCC) cases. The gene expression profiles of IGFBP-2, IGF-1, IGF-1R, PTEN, MDM2, AKT1 and TP53 were determined in three cervical tissue samples each from normal cervix, human papillomavirus (HPV)-infected LGCIN, HGCIN and SCC, using Human Transcriptome Array 2.0. Results: IGFBP-2 protein was highly expressed in the cytoplasm of SCC cells compared to normal cervix (p = .013). The expression was not significantly associated with CIN grade or SCC stage. Transcriptomics profiling demonstrated upregulation of IGFBP-2 and TP53 in HGCIN and SCC compared to normal cervix. IGF-1, IGF-1R and PTEN genes were downregulated in all histological groups. IGF-1 gene was significantly downregulated in SCC (p = .031), while PTEN gene was significantly downregulated in HGCIN (p = .012), compared to normal cervix. MDM2 and AKT1 genes were downregulated in LGCIN and HGCIN, while upregulated in SCC. Conclusion: In cervical carcinogenesis, IGFBP-2 appears to play an oncogenic role, probably through an IGFindependent mechanism.